EARLY DETECTION OF ANEMIA IN ADOLESCENT GIRLS THROUGH NUTRITIONAL STATUS EXAMINATION AND IRON PANEL ANALYSIS (TIBC, SERUM IRON, IRON SATURATION) - Handayani, Ririn; Anggraeni, Ernawati; Handayani, Yuni; Puspita Sari, Melati; Yuningsih (Universitas Airlangga, 2024)
Introduction. The panel iron analysis is an effort made to screen for anemia in adolescent girls. Adolescents with anemia can experience disturbances in growth and development, behavioral changes, and motor disturbances. In Jember district found that on average 30-40% of female students suffer from anemia. Anemia screening is an effort made to maintain the health of adolescents so that they can grow and develop in accordance with their growth and developmental stages. Aims. The purpose of this study is the early detection of anemia in adolescent girls. Methods. This research is an analytical descriptive study with a cross-sectional approach. Data collection was by examining nutritional status and iron panel examination results. The sampling method was accidental, involving 21 female students. The research was conducted in March 2023. Data analysis used frequency distribution. Result. The results showed that some students were undernourished (42.9%) and severely malnourished (4.8%); 18 students (85.7%) were classified as KEK. Meanwhile, from the iron panel analysis, 10 students (47.6%) had abnormal serum iron levels, 6 students (28.6%) had abnormal transferrin saturation levels, and the majority of the respondents, 20 students (95.2%), had normal TIBC. Conclusion. The conclusion from this study is that there are still many adolescent girls, especially in the school environment, who are undernourished to severely malnourished. This result correlates with the iron panel analysis which found that some adolescent girls were diagnosed with iron-deficiency anemia, characterized by a decrease in serum iron, transferrin, and iron reserves levels, accompanied by an increase in the TIBC.